Supported Lipid Bilayers on Fluorescent Nanodiamonds: A Structurally Defined and Versatile Coating for Bioapplications. (19th September 2018) - Vavra, Jan; Rehor, Ivan; Rendler, Torsten; Jani, Mona; Bednar, Jan; Baksh, Michael M.; Zappe, Andrea; Wrachtrup, Joerg; Cigler, Petr
Abstract: Fluorescent nanodiamonds with nitrogen‐vacancy (NV) centers respond to local changes in electric and magnetic fields. These responses can be read optically as changes in fluorescence. NV centers do not suffer from photoblinking or photobleaching, making nanodiamonds a viable platform for long‐term imaging of processes inside living cells. However, for any bioapplication, the surface of these particles must be modified to prevent aggregation and nonspecific protein adsorption and to effectively transduce the changes in local environment to NV center. Modular biomimetic interface has been developed on nanodiamonds with remarkable sensitivity for relaxometric readout that takes advantage of self‐assembled phospholipid bilayers supported by the nanoparticle surface. This rapid and robust approach provides synthetic pathway to tunable composition, demonstrated by tuning surface charge and content of spin labels on nanodiamond. The supported phospholipid bilayer interface increases the detection sensitivity about one‐order‐of‐magnitude. Also, a theoretical model of the system is provided, which shows excellent agreement with experimental results. Merging biocompatibility, modularity, and outstanding spin sensitivity in one nanomaterial provides a foundation for development of multifunctional nanoparticles suitable for highly sensitive monitoring of local magnetic field fluctuations and paramagnetic species under physiological conditions. Abstract : Nanodiamond coated with supported lipid bilayers is a new composite nanomaterial with biocompatible interface. It is highly modular in composition and surface charge and shows outstanding spin sensitivity of nitrogen‐vacancy centers toward local magnetic field fluctuations.